Are Marbling and the Prediction of Beef Eating Quality Affected by Different Grading Sites? - Liu, Jingjing; Pogorzelski, Grzegorz; Neveu, Alix; Legrand, Isabelle; Pethick, David; Ellies-Oury, Marie-Pierre; Hocquette, Jean-François (Frontiers in Veterinary Science, 2021)
For European abattoirs, the preferred carcass grading site is at the 5th rib and cutting at the 10th rib as in Australia could lead to a lower economic value of the carcass. Therefore, the objective of this study was to compare the grading scores of marbling, meat and fat color on M. longissimus thoracis et lumborum at the 5th and the 10th thoracic vertebrae. Consequences on the prediction of beef eating quality using the Meat Standards Australia (MSA) grading scheme were also evaluated for cull cows, which produce the majority of beef consumed in France. Carcasses from 208 French cattle mainly Limousine cows were graded according to the Australian Beef Chiller Assessment System (ABCAS) used for the implementation of the MSA system. The results indicate that there was no significant difference in marbling score, between the 5th rib and the 10th rib, and hence in MSA index and in the global quality scores (MQ4) calculated from marbling values from either the 5th or the 10th rib. However, meat color at the 10th rib was significantly darker than at the 5th rib (P<0.05) and fat color at the 10th rib was significantly yellower than at the 5th rib (P<0.001). The results of this study suggest that grading of marbling can be conducted on M. longissimus thoracis et lumborum at the 5th thoracic vertebrae for a routine use of the MSA system in France and more generally in Europe. However, further investigation and adjustment would be needed for other critical carcass MSA scores (such as rib fat thickness) while respecting European carcass quartering practices.